Design of a Safe Security System Based on Internet of Things Using Face and Fingerprint Detection - Pitaloka, Nadila; Pardede, A M H; Husnul Khair (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
Traditional safe security systems usually use manual keys and a combination of numbers or passwords to open the safe. This system has several disadvantages such as being easy to break into, cumbersome, and the owner easily loses the key, even forgets the password needed to open the safe, which causes the safe to be unable to open. This research develops an Internet of Things (IoT)-based safe security system that uses two security options to open the safe, namely face detection and fingerprint authentication to increase security against unauthorized access with a prototype method. The system uses the ESP32-CAM to capture facial images and send them to the Telegram app for manual verification by the owner, while the fingerprint sensor ensures only registered users can open the safe. Arduino Uno serves as the main microcontroller to manage the integration between components such as ESP32-CAM, fingerprint sensor, relay, solenoid lock, LCD, and buzzer. The test results show that this system is effective in providing security to the safe through notifications, although it still relies on manual verification of faces via Telegram and requires a stable internet connection, and fingerprints that have been registered are successfully implemented. Further development is recommended to automate face recognition and improve the overall performance of the system.